Stories and lessons from the world's leading opera, orchestra librarians, and music archivists. - Lo, Patrick; Sutherland, Robert; Hsu, Wei-En; Girsberger, Russ (Emerald Publishing, 2022)
The collection Stories and Lessons from the World's Leading Opera, Orchestra Librarians, and Music Archivists, explores the current trends and practices in the field of music performance librarianship. A helpful resource to librarians, and archivists in a variety of situations in the world of performing arts.